Women in Translational Medicine: Tools to Break the Glass Ceiling - Bots, Sophie H.; Zuidgeest, Mira G. P.; Gohar, Aisha; Eikendal, Anouk L. M.; Petrelli, Alessandra; van Os-Medendorp, Harmieke; van der Schaaf, Marieke F.; van Sorge, Nina M.; van Wijk, Myriam; Middendorp, Sabine; Speksnijder, Caroline M.; Klipstein-Grobusch, Kerstin; et al. (Frontiers in Medicine, 2018)
Despite the recent movements for female equality and empowerment, few women occupy top positions in scientific decision-making. The challenges women face during their career may arise from societal biases and the current scientific culture. We discuss the effect of such biases at three different levels of the career and provide suggestions to tackle them. At the societal level, gender roles can create a negative feedback loop in which women are discouraged from attaining top positions and men are discouraged from choosing a home-centred lifestyle. This loop can be broken early in life by providing children with female role models that have a work-centred life and opening up the discussion about gender roles at a young age. At the level of hiring, unconscious biases can lead to a preference for male candidates. The introduction of (unbiased) artificial intelligence algorithms and gender champions in the hiring process may restore the balance and give men and women an equal chance. At the level of coaching and evaluation, barriers that women face should be addressed on a personal level through the introduction of coaching and mentoring programmes. In addition, women may play a pivotal role in shifting the perception of scientific success away from bibliometric outcomes only towards a more diverse assessment of quality and societal relevance. Taken together, these suggestions may break the glass ceiling in the scientific world for women; create more gender diversity at the top and improve translational science in medicine.